This action might not be possible to undo. Are you sure you want to continue?
R. Wald Autumn, 2002
Problem Set II Solutions
1) Let L(q, q; t) be a Lagrangian [where, as in class, “q” stands for (q1 , . . . , qn )]. ˙ Suppose we introduce new coordinates (Q1 (q), . . . , Qn (q)) on conﬁguration space. Relate the new momenta, P , to the “old” momenta p and show that ˙ ˙ i Pi Qi = i pi qi . (For the purposes of this problem, it is convenient to view all quantities as functions of the independent variables (q, q).) ˙ The momentum has the form: pi = ˙ ∂L ∂L ∂ Qj ∂L ∂Qj = + ˙ ∂ qi ˙ ˙ ∂Qj ∂ qi ˙ ∂ Qj ∂ qi (1)
(There is an implied sum over double indices in the above equation and those to follow.) But the second term is zero because the Qi ’s are functions only of qi . Because of this we also have that: ∂Qj ˙ qi ˙ Qj = ∂qi So: ˙ ∂ Qj ∂Qj = ∂ qi ˙ ∂qi Thus the new momentum Pi is related to the old by the formula: pi = We also immediately have: p i qi = Pj ˙ ∂Qj ˙ qi = Pj Qj ˙ ∂qi (5) ∂L ∂Qj ∂Qj = Pj ˙ j ∂qi ∂qi ∂Q (2)
Recall that there is an implied sum over double indices. 2) (a) Show that the Euler-Lagrange equations for the Lagrangian 1 dx 2 e dx L= m − eφ + A · 2 dt c dt yield the usual Lorentz force equations of motion of a charged particle in an electromagnetic ﬁeld. 1
(b) From equation 6 above we know that: ˙ e p = mx + A c Thus. where E is the electric ﬁeld.(b) Obtain the corresponding Hamiltonian formulation of the problem. Write out Hamilton’s equation of motion and show explicitly that they also are equivalent to the usual Lorentz force law. so: (11) e˙ ¨ mx = eE + x × B c which is the Lorentz Force Law. p − eA p − eA m p − eA 2 e c c c ˙ H =p·x−L=p· −[ ( ) − eφ + A · ( )] m 2 m c m which gives 1 p2 ep · A 1 (eA)2 H = (1 − ) + (−1 + 1 − 1) + (− + 1) + eφ 2 m mc 2 mc2 p2 ep · A (eA)2 = − + + eφ 2m mc 2mc2 2 (12) (13) (14) . The second term can be calculated as follows: xj ∂i Aj − xj ∂j Ai = xj ∂l Ak (δli δkj − δlj δki ) = xj ∂l Ak ( ˙ ˙ ˙ ˙ But ∂l Ak lkm lkm ijm ) (10) = Bm and xj Bm ˙ ijm ˙ = (x × B)i . (a) First calculate the conjugate momenta: ∂L e = m x i + Ai ˙ ∂ xi ˙ c The ”force” term is: ∂φ e ˙ ∂A ∂L = −e + x· ∂xi ∂xi c ∂xi So the Euler-Langrange equations are: d e ∂φ e ˙ ∂A (mxi + Ai ) = −e ˙ + x· dt c ∂xi c ∂xi (7) (6) (8) Subtracting the time derivative of A from both sides and using the chain rule we have: ∂φ e ∂Ai e ˙ ∂A e ˙ − ]+ x· − (x · )Ai (9) mxi = [−e ¨ ∂xi c ∂t c ∂xi c The ﬁrst term in brackets is eEi .
y(λ). thus. treat (t. i. one cannot eliminate the q’s in favor of ˙ p’s. − . − ) dλ dλ dλ dλ q˙µ = uµ = ( 3 (18) (19) . z) as the “degrees of freedom” and λ as “time”. it is much more in keeping with the “covariant” nature of the theory to treat all four spacetime coordinates (t. (a) Show that the Lagrangian L = −m dt dλ 2 dx − dλ 2 1 2 yields the correct equations of motion for a free particle. y. (In keeping with the above remark. thus Hamilton’s equations also reduce to the Lorentz Force Law. (c) Nevertheless. z(t) in a 3-dimensional conﬁguration space (with t the time coordinate of a particular global inertial coordinate system). obtain a (constrained) Hamiltonian formulation for the free relativistic particle by the procedure described in class. x. 3) In the context of special relativity. x. are not independent. − . z(λ) in a 4-dimensional conﬁguration space (with λ an arbitrary parameter along the path) rather than as a curve x(t). . (a) First.) (b) Show that the conjugate momenta satisfy the relation p2 − (p2 + p2 + p2 ) = m2 t x y z and. and thus to describe particle motion as a path t(λ). with α = dt/dλ. z) on an equal footing. y. ) dλ dλ dλ dλ dt dx dy dz q˙µ = uµ = ( .e. y(t). x(λ). let’s deﬁne some simpler notation: dt dx dy dz . .Hamilton’s equations are: ∂H pi eAi = − ∂pi m mc 2 ep ∂ A e ∂A ∂φ ∂H pi = − ˙ =+ · − A· −e ∂xi mc ∂xi mc2 ∂xi ∂xi xi = ˙ Using the equation for x we can write the p equation as: ˙ ˙ d eAi ˙ e ∂ A − e ∂φ (mxi + ˙ )=x· dt c c ∂xi ∂xi (17) (15) (16) This is the same as equation 8 above.
we see that: pµ pµ = m2 uµ uµ [uν uν ]− 2 [uσ uσ ]− 2 = m2 uµ uµ [uν uν ]−1 = m2 4 1 1 (29) . Thus. If I choose a new λ = f (λ) then Pµ is: Pµ = −mβuµ [βuν βuν ]− 2 = −muµ [uν uν ]− 2 1 1 (24) where β = dλ . which we will call Pµ . Then the Lagrangian is now expressed as: L = −m[uµ uµ ] 2 The momenta are: 1 (20) 1 ∂L = −muµ [uν uν ]− 2 (21) µ ∂u Since the coordinates do not explicitly appear in L. which allows us to set uµ uµ to a constant (which is 1 if λ is the proper time). (b) Using equation 21. we see that the function in brackets is f (λ). the equation of motion is: 1 d (−muµ [uν uν ]− 2 ) = 0 (22) dλ which says the term in parenthesis is a constant. So we can choose λ equal to the proper time τ and equation dλ 23 becomes: dqµ Pµ = −m (25) dτ which is the familiar expression for the (constant) momentum of a relativistic particle. one can choose a new λ that is aﬃne.where q µ are the coordinates and uµ are the ﬁrst derivatives with respect to λ. choosing λ aﬃne gives u˙µ = 0. pµ = Pµ = −muµ [uν uν ]− 2 1 (23) Note that this expression is independent of the parametrization λ along the world-line. It is easy to show that if λ is not aﬃne. we will get (after dividing by −m): 1 3 u˙µ [uν uν ]− 2 − uµ [uν uν ]− 2 uσ u˙σ = 0 (27) This leads to: u˙µ = [ uσ u˙σ ]uµ u ν uν (28) After noticing that the left-hand side of equation 24 is u˙ν . The parameter λ is aﬃne if the function f (λ) = 0 in the following equation: uµ ∂µ uν = f (λ)uν (26) Carrying out the derivative in equation 22.
We choose one of them (α = dλ ) to serve as a non-dynamical constraining variable. pi ) 1 (30) where i runs over the spatial variables. we cannot eliminate all of the uµ in dt favor of them. Deﬁne γ = α[uµ uµ ]− 2 (note that this has no α dependence.) Thus: H = p0 α − 1 pi pi µ 1 pi pi α α [u uµ ] 2 + m[uµ uµ ] 2 = p0 α − +m m m γ γ (31) Note that −pi pi = p2 and that: (γm)2 = Thus: H = p0 α + α p 2 + m2 So Hamilton’s equations read: qi = ˙ ∂H pi =√ 2 = ∂pi p + m2 ∂H pi = − ˙ ∂qi ∂H = p0 + p 2 + m2 ∂α pi γm =0 =0 (34) (35) (36) (33) m2 1 − v2 + v2 = m2 = m2 + m2 (γv)2 = m2 + p2 1 − v2 1 − v2 (32) 5 . Thus we have the Hamiltonian: H = p0 α + pi ui − L(α.(c) Since the pµ are not independent.